2017
DOI: 10.1002/2017wr020412
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Graphical Model of the California Reservoir System

Abstract: The recent California drought has highlighted the potential vulnerability of the state's water management infrastructure to multiyear dry intervals. Due to the high complexity of the network, dynamic storage changes in California reservoirs on a state‐wide scale have previously been difficult to model using either traditional statistical or physical approaches. Indeed, although there is a significant line of research on exploring models for single (or a small number of) reservoirs, these approaches are not ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…More recent developments of variational methods are described in Jordan [ 50 ]. Callies [ 51 ] and Callies and Scharfe [ 52 ] applied graphical modeling for analyzing interaction structures from water quality observations; Taeb et al [ 53 ] used it to characterize dependencies among water reservoirs. The specific aspect in this study is that we do not apply the method to observed variables but rather to a set of parameters in a process-oriented simulation model that were calibrated in order to adjust model output (time series of one single variable) to its observed counterpart.…”
Section: Methods Of Bayesian Analysis and Complexity Reductionmentioning
confidence: 99%
“…More recent developments of variational methods are described in Jordan [ 50 ]. Callies [ 51 ] and Callies and Scharfe [ 52 ] applied graphical modeling for analyzing interaction structures from water quality observations; Taeb et al [ 53 ] used it to characterize dependencies among water reservoirs. The specific aspect in this study is that we do not apply the method to observed variables but rather to a set of parameters in a process-oriented simulation model that were calibrated in order to adjust model output (time series of one single variable) to its observed counterpart.…”
Section: Methods Of Bayesian Analysis and Complexity Reductionmentioning
confidence: 99%
“…More recent development of variational methods are described in Jordan (2004). Callies (2005) and Callies and Scharfe (2015) applied graphical modelling for analysing interaction structures from water quality observations, Taeb et al (2017) used it to characterize dependencies among water reservoirs.…”
Section: Gaussian Graphical Models (Ggms)mentioning
confidence: 99%
“…The main goal for our "California Umbilical Cord" must be the essential restoration of the San Joaquin River's pre-World War II volume of freshwater flow into the overstressed Delta Region and San Francisco Bay by using its watery augmentation through North Coast freshwater importation via submarine pipeline and connected overland pipeline to San Luis Reservoir. Coincident with this singular environmental maintenance goal must be the reformation or reorganization of the Eel River [19][20][21], Russian River and Rogue River; the documented response of North Coast residents and their representatives, in the past, has been hostile to development plans affecting these California rivers. On 18 July 2018, California's Supreme Court removed Proposition 9 from the General [State-wide] Election Ballot slated for 6 November 2018.…”
Section: Submarine Freshwater Pipeline State Of California (Usa)mentioning
confidence: 99%